FACTORS AFFECTING COLLATERAL VALUE AT THE INDONESIAN STATE BANK IN THE PAPUA REGION - Rusmini Rusmini; Elisabet Siahaan; Handy Octavianus (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The importance of accuracy in collateral valuation as one of the main instruments in maintaining banking health, particularly in controlling the non-performing loan (NPL) ratio. Inaccuracies in collateral analysis, which lead to overvaluation or the use of assets that do not have strategic market value, have the potential to cause difficulties in collateral execution and increase the risk of bank losses. This study aims to examine and analyse the factors that influence collateral value at Bank Negara Indonesia (BNI) in the Papua region. The research method uses a quantitative descriptive approach. The research population consists of data on 150 BNI Griya Multiguna consumer credit debtors, specifically residential debtors. A sample of 60 data points was obtained using purposive sampling. The data was obtained from five BNI branches in the Papua Region in the form of land legality, land area, building area, building legality, and building construction. The results of multiple linear regression show that land legality, building legality, and building area have a positive and significant effect on collateral value, while land area and building construction have a positive effect but are not statistically significant. The results of this study confirm that legal aspects, including land legality and building legality, as well as building area, are the main determinants of collateral value for residential consumer loans in the Papua Region. These findings are important for banks, appraisers, and stakeholders in the management of residential property-based loans, and encourage more accurate evaluations to minimise the risk of non-performing loans in the Papua region, ultimately benefiting the Government of the Republic of Indonesia.